Nose-to-Brain Delivery of Antioxidants as a Potential Tool for the Therapy of Neurological Diseases - Maria Cristina Bonferoni; Giovanna Rassu; Elisabetta Gavini; Milena Sorrenti; Laura Catenacci; Paolo Giunchedi (MDPI AG, 2020)
Oxidative stress has a key role in the pathogenesis of neurodegenerative disorders such as Alzheimer's, Parkinson's, and Huntington's diseases and can be an important cause of the damages in cerebral ischemia. Oxidative stress arises from high levels of reactive oxygen species (ROS). Consequently, on this rational base, antioxidants (many of natural origin) are proposed as potential drugs to prevent ROS noxious actions because they can protect the target tissues from the oxidative stress. However, the potential of antioxidants is limited, owing to the presence of the blood-brain barrier (BBB), which is difficult to cross with a consequent low bioavailability of the drug into the brain after systemic (intravenous, intraperitoneal, oral) administrations. One strategy to improve the delivery of antioxidants to the brain involves the use of the so-called nose-to-brain route, with the administration of the antioxidant in specific nasal formulations and its passage to the central nervous system (CNS) mainly through the olfactory nerve way. In the current literature, many examples show encouraging results in studies carried out in cell cultures and in animal models about the potential neuroprotective effects of antioxidants when administered through the nose. This review concerns the nose-to-brain route for the brain targeting of antioxidants as a potential tool for the therapy of neurological diseases.